Exploring natural therapy for chronic heart failure: experience in traditional Chinese medicine treatment before 2022 - Pan, Li-Ping; Zhu, Lanxin; Wang, Bing-Xue; Li, Yi-Qi; Gao, Li; Zhao, Hui Hui (Frontiers in Medicine, 2025)
BackgroundTraditional Chinese medicine has great advantages in improving symptoms of CHF such as chest tightness, shortness of breath, and fatigue. In addition, some traditional Chinese medicines can be used as both medicine and food, which have good effects on the prevention and treatment of CHF patients at home.MethodA comprehensive search across China National Knowledge Infrastructure (CNKI), Wanfang, and Wei Pu (VIP) databases was conducted to retrieve pre-2022 literature related to CHF. After standardization, frequency analysis and Apriori algorithm were used to analyze these data.ResultAmong 626 effective medical records, Fuling, Huangqi, and Danshen are the most commonly used herbs; The medication for chest tightness is closely related to Tinglizi; The medication for palpitations is closely related to Guizhi, Fuzi, Zhigancao, and Wuweizi; The medication of fatigue and poor appetite is closely related to Huangqi and Baizhu; The medication for lower limb edema is closely related to Fuling and Tinglizi; The medication for coughing is closely related to the use of Tinglizi, Wuweizi, Kuxingren, and Sangbaipi; Insomnia is closely related to Suanzaoren and Dazao.ConclusionThe components in traditional Chinese medicine that have anti heart failure effects and reliable evidence can be potential candidates for drug discovery, while dietary therapeutic herbs such as Fuling, Huangqi, Danshen, and Zhigancao can be developed as health products.